Routine VDRL Test in Pregnant Women: How Justified Is It? (Ibrahim Cardiac Medical Journal, 2021)
Background & objective: The present study was undertaken to justify the role of routine antenatal screening for syphilis using the Venereal Disease Research Laboratory (VDRL) test in Bangladeshi pregnant women.Methods: The study was carried out in the Department of Gynecology & Obstetrics Inpatient and Outpatient, Dhaka Medical College Hospital (DMCH) and selected Private Clinics over a period of 6 months between January 2016 to June 2016. Pregnant women attending at the above-mentioned places during the study period were the study population. A total of 371 women attending at antenatal clinic at OPD or admitted in the Inpatient Department of DMCH were consecutively included. The outcome variable was outcome of VDRL test.Result: In the present study, the mean age of the pregnant women was 24.3 years. In terms of occupation, housewife comprised the main bulk (78.8%). About 64% were multigravida and 60% were primipara. Of the 371 pregnant women subjected to VDRL test, only 4(1.1%) exhibited reactive. About one-third of the women had history of past abortion. Of them two-thirds had experienced abortion once. Of the aborted cases 57% were spontaneous and 43% induced. Ten percent of the women gave the history of delivering dead baby. Three-quarters of the dead babies were fresh, 22.2% had skin lesion and only one was macerated. Half of the women had history of vaginal discharge, 27.2% itching in vagina and vulva and 17% dysuria. However, very few husbands had dysuria, pus discharge through urethra or ulcer in the genital region. About 10% of women gave the history opthalmia neonatrum in their children born in the past. History of dysuria was rare (0.8%), but pus discharged from urethra of their husbands was 12.1%. HbsAg was found positive in 5(1.3%) cases and pus-cell in urine in 41(11.1%) cases.Conclusion: The study concluded that pregnant women with VDRL test positivity in Bangladeshi population are low and, as such, the role of routine antenatal screening for syphilis with VDRL test should be re-considered.Ibrahim Card Med J 2020; 10 (1&2): 89-95